PEMBUATAN PROTOTIPE PENGERING BATUBARA UNTUK MENGURANGI MOISTURE CONTENT PADA PLTU - Mangestiono, Wiji (Gema Teknologi, 2014)
Wiji Mangestiono, in paper prototype development of coal dryer to reduce moisture content on power plant explain that the percentage of coal use in the power industry in Indonesia has increased during the period of the last ten years. This policy is taken by the government by at least two considerations, namely: the higher world oil prices so that the price of electricity per kwh increase in addition Indonesia itself is the world's largest coal producer with serial number to six so that the transfer of fuel oil to the coal is considered very right. There is a fundamental problem that must be observed that coal mining in Indonesia in general have a low- rank quality with sub - categories butuminus and lignite which has a low calorific value (below 6100 kcal / kg ) and moisture content (moisture content) relatively high (40%). This is exacerbated by the way the coal deposit which is usually placed on the page (coal yard). Low-rank coal with pores relatively greater will more easily absorb water during the rainy season so that the moisture content will be even greater. The use of coal in Rembang reached 1.3 million tons / year. Heat loss due to the use of coal with a high moisture content reaches 300 billion kcal per year or equivalent to coal with a calorific value of 50 thousand tons or the equivalent of cash also 30 billion rupiah. After observing the phenomenon in Rembang the researchers plan to create a prototype coal heaters with a capacity of 100 kg / hour in the hope of getting a concept to eliminate or minimize heat loss as described. Heating devices planned screw -shaped drum with a player in it which serves stirring granulated coal. The hot air is taken from the flue gas is sprayed into the drum. The independent variable of this study is the screw rotational speed and the speed and temperature of the hot air flow. Coal is expected after discharge from the dryer may have a water content below 10 % as high quality coal (anthrasit). Keyword : coal, moisture content, dryers